"No Child's Play": Child Narrators, Transitional Objects, and Embodied Trauma in Nancy Huston's Lignes de faille - Tremblay Ponnou-Delaffon, Erin (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2024)
Drawing on theories of childhood development by Janusz Korczak, Donald Winnicott, and George Eisen, this article examines play objects as a narrative trope for communicating embodied memory and transgenerational trauma. I focus on the novel Lignes de faille (Fault Lines, 2006) to demonstrate how Nancy Huston exploits the creative potential of unauthoritative child narrators through their relationship to a network of transitional play objects. Paradoxically, “[t]his is no child’s play,” to adopt Korczak’s expression, which would inspire a Yad Vashem exhibition on children of the Shoah. As I contend, recourse to child narrators allows Huston to tellingly critique adults’ war “games” and expose violence’s lasting mark on individuals, families, and societies. Situating Lignes de faille within the transnational writer’s wider oeuvre, this article further invites a conversation with related contemporary, global Holocaust narratives which prominently feature transitional play objects. Such a perspective ultimately underscores the motif’s stakes for Huston’s understanding of the human person and of artistic creative “play,” as well as for issues of genre, audience, and representability in Holocaust literature.